Shadow Boxing the Ridiculous: Riding on the Moral Arc of the Universe - Townes, Emilie M. (Journal of the Society of Christian Ethics, 2025)
Primarily, my work has focused on the study of the nature of evil(s). I explore it as an inter-structural phenomenon and its impact on individuals and groups through its dehumanizing effects. In this essay, I use the concepts of the shocking, the outrageous, and the indecent to frame and structure a critique of the academic world’s genuine deficiencies in addressing oppression and the role that we, as ethicists, may play in this. Given the current onslaughts on higher education, it is timely that I argue that ethicists should integrate the inclusion of organic inquisitiveness that is often found in “minority” communities to help expand both our theoretical and epistemological analyses. In essence, we should acknowledge and incorporate not only the plurality of different religious traditions and points of view but explore varying cultural perspectives in order to stop perpetuating rationalized inequity that can be both subtle and brutally dehumanizing.